Evaluasi Penerapan Standar Akuntansi Pemerintah Berbasis Akrual Dalam Penyusunan Laporan Operasional Pada Badan Pengelola Dan Aset Daerah Kabupaten Kupang - Fransiskus Marlon Reu (Universitas Katolik Widya Karya Malang, 2024)
This research aims to determine the suitability of the application of government accounting standards in preparing operational reports at the Regional Financial and Asset Management Agency of Kupang Regency, whether they are in accordance with the Government Accounting Standards Statement Number 12 contained in Government Regulation Number 71 of 2010. This research was conducted at the Financial Management Agency And Regional Assets of Kupang Regency. In this research, the formulation of the problem is to determine whether the application of government accounting standards in preparing operational reports at the Regional Financial and Asset Management Agency of Kupang Regency is in accordance with the Government Accounting Standards Statement Number 12 contained in Government Regulation Number 71 of 2010. Data in the research This is primary data in the form of interviews with the head of the agency and head of the accounting section of BPKAD Kupang Regency and operational reports for 2020. The method used in the research is a qualitative descriptive analysis method. Qualitative descriptive analysis, namely analyzing, describing and summarizing various conditions from various data collected regarding operational reports at the Regional Financial and Asset Management Agency of Kupang Regency, then adapted to PSAP No. 12 concerning operational reports